Effect of post-polymerization heat treatment on a denture base acrylic resin: histopathological analysis in rats - Meister, Lissandra M.; Kovalik, Ana Cristina; Pellissari, Cláudia Viviane Guimarães [UNESP]; Bail, Michele; Campagnoli, Eduardo Bauml; Jorge, Janaina Habib [UNESP]; Campanha, Nara Hellen (My University, 2015)
This work examined the histological effects, on the rat palatal mucosa, of a denture base acrylic resin, submitted or not to a post-polymerization heat-treatment. Methods: Fifteen adult female Wistar rats, with sixty days old, weighting 150 g – 250 g were divided in G1: animals being maintained under the same conditions as the experimental groups following described, but without the use acrylic palatal plates (control group); G2: use of heat-polymerized acrylic resin palatal plates made of Lucitone 550; G3: use of palatal plates identical to G2, but subjected to a post-polymerization treatment in a water bath at 55°C for 60 min. The plates covered all the palate and were fixed in the molar region with light-cured resin, thus being kept there for 14 days. After the sacrifice, the palate was removed, fixed in formaldehyde 10% and decalcified with EDTA. Sections were stained using haematoxylin and eosin. Images in duplicate were made from the central region of the cuts, to measure the thickness (μm) of the keratin layers (TKC), epithelium total (TET) and connective tissue (TCC). Statistical analyses were carried out by one-way ANOVA and Tukey post-tests (α=0.05). Results: According to the results there was significant difference in the thickness of keratin between G2 and G3, with G1 having the intermediate value and similar to the other groups. There was a significant difference in the connective tissue with G3 <G1 <G2 (p <0.0001). Conclusion: Regarding the total epithelium, group G3 presented a statistically significant difference with both G1 and with G2 (p <0.0001), which were similar to each other. When using the proposed heat treatment it was found to be effective, from the viewpoint of biocompatibility, for the acrylic resin denture base investigated.
Keywords: Biocompatibility; Acrylic Resin; Wistar Rat; Palatal Mucosa; Palatal Appliances